In the Service of Good Journalism and Audience Interests? How Audience Metrics Affect News Quality - Fürst, Silke (2020)
A large and growing body of literature shows that audience metrics exert a significant influence in many newsrooms around the world. Scholars assume that this might affect the quality of news, but findings on how audience metrics influence news quality and media performance are scattered. Based on a widely used set of news quality criteria, this article is the first to focus on this question. It reviews and discusses the existing findings by considering the influence of audience metrics across four analytical dimensions: A) the allocation of resources and recognition; B) the volume, practices and rhythms of news production; C) the selection and placement of topics; and D) the formats and styles of news presentation. The analysis reveals that journalists’ use of audience metrics has a mainly negative impact on news quality. This effect is the result of both the growing economic pressures on newsrooms and a dominant rhetoric that equates measures of audience size with audience interests and good journalistic work.